A comparative analysis of patient satisfaction with various methods of digital smile design and simulation - Mahsa Babaei; Mehrdad Kazemian; Mehrdad Barekatain (Dental Research Journal)
Background: Digital smile design (DSD) is a technique that utilizes the scientific methods and advanced software to design patients’ smiles, presenting the visualized smile map directly to the patient. However, patients may not always find the proposed smile satisfactory or feel a sense of alignment with it. To address this concern, dentists have been integrating the tooth shape with the overall facial shape and other parameters to develop a personalized smile plan for each patient. Materials and Methods: This study employed a descriptive-analytical, cross-sectional research design conducted during the summer and fall of 2022. This research sought to evaluate patient satisfaction levels associated with three distinct DSD techniques: Visagism, Proportional, and Stepwise Comprehensive. A sample of 20 participants, evenly split between males and females, was selected, all of whom were seeking smile design treatment and did not present with skeletal, jaw, facial, or periodontal complications. Interviews were conducted to analyze personality and temperament, and smile maps were created utilizing the Visagism, Stepwise Comprehensive, and Proportional methods. Subsequently, patients evaluated the designs produced by all three methods and completed a satisfaction questionnaire. Nonparametric statistical tests, namely the Kruskal–Wallis test and post hoc Bonferroni tests, were used to examine the research hypotheses at a significance level of 0.05. Results: The results indicated a high level of satisfaction with all three DSD methods, with no statistically significant differences observed among them. These results suggest that all three approaches effectively met the patients’ expectations and preferences. Conclusion: The outcomes of this study have practical implications for dental professionals engaged in DSD, potentially enhancing patient experiences and treatment outcomes. Further research in this domain may explore the additional factors that could influence patient satisfaction and refine the DSD process.